2007
DOI: 10.1111/j.1365-2036.2006.03191.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of immediate‐release omeprazole oral suspension, delayed‐release lansoprazole capsules and delayed‐release esomeprazole capsules on nocturnal gastric acidity after bedtime dosing in patients with night‐time GERD symptoms

Abstract: SUMMARY BackgroundGastro-oesophageal reflux disease (GERD) patients on proton pump inhibitors before breakfast or dinner have acid recovery at night. Bedtime immediate-release omeprazole (IR-OME) demonstrated better control of nocturnal pH than pantoprazole before dinner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 20 publications
(28 reference statements)
8
42
0
2
Order By: Relevance
“…The percentage of time with gastric pH >4 for the entire 24-h period was 43.6% after treatment with IR-OME vs. 59% with esomeprazole (p<0.001) and 27.8% with lansoprazole (p<0.001), when compared with both IR-OME and esomeprazole (Table 2). 14 This study further supports the longstanding suggestion that delayed release PPIs are not optimally effective when given at bedtime. Lansoprazole offered a slow onset of overnight control with little increase the next day.…”
Section: Immediate-release Omeprazolesupporting
confidence: 81%
See 1 more Smart Citation
“…The percentage of time with gastric pH >4 for the entire 24-h period was 43.6% after treatment with IR-OME vs. 59% with esomeprazole (p<0.001) and 27.8% with lansoprazole (p<0.001), when compared with both IR-OME and esomeprazole (Table 2). 14 This study further supports the longstanding suggestion that delayed release PPIs are not optimally effective when given at bedtime. Lansoprazole offered a slow onset of overnight control with little increase the next day.…”
Section: Immediate-release Omeprazolesupporting
confidence: 81%
“…13 An open-label, randomized, crossover study (N=54) compared intragastric pH with IR-OME suspension 40 mg, lansoprazole 30 mg, and esomeprazole 40 mg given at bedtime (10:00 P.M.) on an empty stomach for 7 days. 14 In the first half of the nighttime, intragastric pH >4 were higher after IR-OME compared to esomeprazole or lansoprazole (p<0.001, both comparisons). 15 Acid control with IR-OME was significantly better than lansoprazole (p< 0.001) and comparable to esomeprazole for the entire nighttime period.…”
Section: Immediate-release Omeprazolementioning
confidence: 91%
“…There was significant difference in oesophagitis healing between group A & B. Katz P et al showed bed time IR-OMEP provided more rapid control of night time gastric pH and decrease in nocturnal acid break through compared to lansoprazole & esomeprazole. Nocturnal acid control with IR-OMEP was superior to lansoprazole & esomeprazole 27 .…”
Section: Gerd (N=69)mentioning
confidence: 86%
“…The enteric delayed-release dosage form of LPZ has been reported to be unable 4030 alai and lin to efficiently suppress nocturnal acid secretion in the event of gastroesophageal reflux disease. 6,7 Nocturnal acid breakthrough frequently occurs in patients with gastroesophageal reflux disease during the first half of the sleeping period, and affects sleep quality and daytime functioning. Eudragit ® RS100 and poly(lactic-co-glycolic acid) (PLGA) polymers have been used as drug carriers.…”
Section: Introductionmentioning
confidence: 99%